Analisis Pesan Moral Dalam Film “2037” - Sinta Apriani; Choiriyah; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Film is a communication medium in the form of entertainment. Apart from containing entertainment and being a communication medium, films are also full of meaningful values such as social, political, moral, religious and other values. Like in the film 2037, there is a moral message to be conveyed, related to the singing experienced by a female rapidana. This 126 minute film is directed by Mo Hong Jin. To find out the moral message in the film 2037, researchers formulated two problems as follows: (1) Are there scenes that contain a moral message in the film 2037? (2) What types of moral messages are contained in the film 2037? The method used is a qualitative approach with observation and documentation data collection techniques. The research analysis technique that the researcher uses is Charles Sanders Peirce's semiotic analysis which divides the discussion into signs, objects and interpretants. Researchers analyzed the selection of texts and images related to moral messages. In this research, it was concluded that in the film 2037 there are 9 scenes that contain a moral message. Where the representation/sign contains 6 scenes of the qualisign type, 1 scene of the sinsingn type and 3 scenes of the legisign type. Meanwhile, the objects are all index types and the interpretants are all rheme types. Of the nine scenes in the film 2037, the moral messages contained vary from love, self-respect, care, disappointment, sympathy, mutual help, responsibility, selfishness and gratitude.